1995
DOI: 10.1093/ajcp/103.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Oncogenic Expression in Malignant Effusions as a Possible Method to Enhance Cytologic Diagnostic Sensitivity:An Immunocytochemical Study of 87 Cases

Abstract: The diagnostic ability of cytological preparations can be hampered by specimen inadequacy and the presence of representative cells, which may result in a diagnostic accuracy of only 70%. An immunocytochemical battery (ICC), which included anti-p53, anti-c-erbB-2, and B72.3 MoAbs, was used to enhance sensitivity in 87 specimens of body effusions. Thirty-six cases were positive for malignancy using conventional cytology. Forty cases were negative and 11 cases were inconclusive or had an equivocal diagnosis. Sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Confirming our data, a higher incidence of ErbB2 overexpression in breast malignant effusions as compared to primary tumor was reported in 2 independent immunocytochemical studies, with respectively 51% and 56% of positive specimens. 47,48 Moreover, ErbB2-specific ELISA staining of effusion cells showed that ErbB2 is a potential tumor marker for the diagnosis of pleural effusion in lung adenocarcinoma. 49 Upregulation of ErbB2 in effusion cells from breast carcinoma patients has been also reported.…”
Section: Purification Of Carcinoma Cells From Malignant Effusionsmentioning
confidence: 99%
“…Confirming our data, a higher incidence of ErbB2 overexpression in breast malignant effusions as compared to primary tumor was reported in 2 independent immunocytochemical studies, with respectively 51% and 56% of positive specimens. 47,48 Moreover, ErbB2-specific ELISA staining of effusion cells showed that ErbB2 is a potential tumor marker for the diagnosis of pleural effusion in lung adenocarcinoma. 49 Upregulation of ErbB2 in effusion cells from breast carcinoma patients has been also reported.…”
Section: Purification Of Carcinoma Cells From Malignant Effusionsmentioning
confidence: 99%
“…Recently immunohistochemical determination of oncogenes was successfully employed to increase diagnostic sensitivity in serous effusions. 9 The p53 gene is a tumor suppressor gene that plays an important role in controlling cell proliferation. Mutation of the p53 gene is a genetic anomaly present almost exclusively in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…6,25 Immunohistochemical determination of p53 protein has been extensively studied in tissue sections, but the literature regarding the application of this method in the study of serous effusions is scarce. 9,31,35 The sensitivity of immunohistochemical determination of p53 protein in serous effusions has ranged from 59% to 83%, and specificity has ranged from 73% to 100%. 9,31,35 The use of anti-p53 antibody with different grades of specificity as well as different methods of fixation and staining procedures may cause these variable staining results.…”
Section: Discussionmentioning
confidence: 99%
“…1 We would like to comment on the fact that the authors of this interesting study did not take into account the presence of nonneoplastic and reactive mesothelial cells in effusions and especially the difficult differential diagnosis of the latter with malignant cells from cancer metastasis or malignant mesothelioma.…”
Section: Differential Diagnosis Of Malignant Effusionsmentioning
confidence: 99%
“…At the same time, I find that few pathology residents have more than a very basic knowledge of gross anatomy. I was therefore interested to read in the interesting article on intraneural perineurioma by Dr. Emory and her colleagues in this Journal, 1 that their largest lesion involved the sciatic nerve from the obturator foramen to the knee. The sciatic nerve has no relationship to the obturator foramen, but leaves the pelvis through the greater sciatic foramen posteriorly.…”
mentioning
confidence: 99%